Fictional Bodies, Factual Reports: Public Inquiries TV Drama and the Interrogation of the NHS. Issue 1 (January 2017) - Bruce, Susan
Abstract : This article addresses the question: 'What can popular culture know?' via an examination of the critique of one British public sector institution (the NHS) articulated through a medical drama aired on another British public sector institution (the BBC). I situate Jed Mercurio's Bodies (2004–6) in the context of political intervention in the NHS over the last 30 years, and explore the relation it bears to two public NHS scandals. I argue that Bodies is highly self-aware in its representation of the changes to professional life occasioned by successive waves of NHS reform, and directly indebted to the events of, and conditions surrounding, the 1990s Bristol heart scandal. I further claim, however, that the series situates the kinds of incompetence and mismanagement that underlay real-life events in Bristol within a fictionalised managerial workspace culture in which many of the recommendations for future practice articulated in the Kennedy Report are already in place. In so doing Bodies offers a proleptic perspective on what can go wrong in the NHS, anticipating in fiction the conclusions of the Francis Reports on the Mid-Staffs scandal, several years before the events unfolding there were exposed to public view. In that process, I conclude, the series lodges a more generalised critique of neo-liberal public sector reform implicitly extendable to other public sector institutions.